Approach for needle insertion into the tibialis posterior: An ultrasonography study. Issue 4 (8th September 2015) - Won, Sun Jae; Yoon, Joon Shik
ABSTRACT: Introduction: To avoid neurovascular damage by needle electrode insertion into the tibialis posterior, we used ultrasonography to determine the proper insertion point based on anatomic landmarks. Methods: Using ultrasonography, the safety window, the corrected safety window, and the depth of the tibialis posterior were measured at 4 points (the upper third and midpoint of the tibia using anterior and posterior approaches) in healthy volunteers. Results: The safety window at the midpoint for the posterior approach was significantly larger than at the other points. The corrected safety window could be defined only at the upper third for the anterior approach and at the midpoint for the posterior approach. Conclusions: Among the 4 points used for needle insertion into the tibialis posterior, the midpoint by the posterior approach may be the most favorable insertion point. The upper third may be better for the anterior approach. Muscle Nerve 53 : 528–531, 2016